2019
DOI: 10.1007/s41042-019-00014-7
|View full text |Cite
|
Sign up to set email alerts
|

Program Logic Modelling and Complex Positive Psychology Intervention Design and Implementation: The ‘Resilient Futures’ Case Example

Abstract: Positive psychology interventions (PPIs) and programs differ markedly in implementation quality. Lower quality implementation is associated with interventions that include multiple components (or PPIs), are delivered across multiple layers (individual, workgroup/ classroom and organisation/school) or agency sites, and include cohorts with heterogeneous or complex needs (e.g., trauma). This paper collectively refers to these interventions as 'complex PPI's' or 'complex programs'. Drawing upon the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Even though some positive psychology models have been proposed to explain how programs achieve their objectives (e.g., Lyubomirsky and Layous, 2013 ; Raymond et al, 2019 ), current practices make it difficult to develop a comprehensive logic model of positive psychology interventions. It has been argued, for example, that current positive psychology interventions are conceived as cohesive units of activity, which limit their development and evaluation (Raymond et al, 2019 ; Pawelski, 2020 ). Through our scoping review, we found that researchers present logical connections between intervention objectives and target populations, but that there is a lack of cohesion and reasoning behind activities implemented and some of the target outcomes measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though some positive psychology models have been proposed to explain how programs achieve their objectives (e.g., Lyubomirsky and Layous, 2013 ; Raymond et al, 2019 ), current practices make it difficult to develop a comprehensive logic model of positive psychology interventions. It has been argued, for example, that current positive psychology interventions are conceived as cohesive units of activity, which limit their development and evaluation (Raymond et al, 2019 ; Pawelski, 2020 ). Through our scoping review, we found that researchers present logical connections between intervention objectives and target populations, but that there is a lack of cohesion and reasoning behind activities implemented and some of the target outcomes measured.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of objectives and target outcomes showed that authors were mostly interested in distal positive effects of interventions on different types of well-being [reducing depression] rather than proximal effects on character strengths [developing optimism to then reduce depression]. Even though some positive psychology models have been proposed to explain how programs achieve their objectives (e.g., Lyubomirsky and Layous, 2013;Raymond et al, 2019), current practices make it difficult to develop a comprehensive logic model of positive psychology interventions. It has been argued, for example, that current positive psychology interventions are conceived as cohesive units of activity, which limit their development and evaluation (Raymond et al, 2019;Pawelski, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needs analysis firstly draws on an extensive study of the scientific literature on mental health and wellbeing interventions. Secondly, it is underpinned by findings and data (published and unpublished) from previous wellbeing studies our research group conducted across population groups including in the general community, within workforces such as health professionals, with older adults, carers, and disadvantaged youths (Raymond et al, 2018(Raymond et al, , 2019van Agteren et al, 2018a;Bartholomaeus et al, 2019). All data that was being used to underpin the needs analysis was subject to ethics approvals issued by the Flinders University Social and Behavioural Research Ethics Committee (SBREC), project numbers (PN) 7834, 7891, 7350, 7358, 7221, 7218, and 8579. The IM framework uses the PRECEDE-PROCEED model (Gielen et al, 2008) to summarise and structure the results of the needs analysis into an actionable logic model.…”
Section: Methodsmentioning
confidence: 99%
“…Within the reorientation of the Resilient Futures program, a program logic model was developed to articulate a hierarchy of short-, medium-, and long-term outcomes, which were categorized against the domains of youth, agency, and agency system. An article has been submitted detailing the scientific evidence underpinning the program logic modeling as a method to support the design and implementation of complex positive psychology programs, including the Resilient Futures program (Raymond, Iasiello, Kelly, & Jarden, 2018). The logic model also articulates the key program components.…”
Section: The Resilient Futures Programmentioning
confidence: 99%